2021
DOI: 10.1186/s13195-020-00764-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and concurrent patterns of regional BOLD dynamics and functional connectivity dynamics in cognitive decline

Abstract: Background The brain’s dynamic spontaneous neural activity and dynamic functional connectivity (dFC) are both important in supporting cognition, but how these two types of brain dynamics evolve and co-evolve in subjective cognitive decline (SCD) and mild cognitive impairment (MCI) remain unclear. The aim of the present study was to investigate recurrent and concurrent patterns of two types of dynamic brain states correlated with cognitive decline. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…Key differences consisted mainly of a decreased co-activation of the BFB with the DMLN, decreased BOLD activity within the DMLN and an increased BOLD activity in the CG in TgF344-AD rats. These results are consistent with similar observations describing changes in the QPP-DMN + in a recent human study (54). Using dynamic FC analyses in healthy controls and patients with subjective cognitive decline, Liang et al observed decreased occurrence of a brain state where DMN was activated, while other networks were deactivated (54), a brainstate which resembles the QPP-DMLN observed in this study.…”
Section: Spatial and Temporal Alterations In Dmln Activity In Adsupporting
confidence: 93%
See 1 more Smart Citation
“…Key differences consisted mainly of a decreased co-activation of the BFB with the DMLN, decreased BOLD activity within the DMLN and an increased BOLD activity in the CG in TgF344-AD rats. These results are consistent with similar observations describing changes in the QPP-DMN + in a recent human study (54). Using dynamic FC analyses in healthy controls and patients with subjective cognitive decline, Liang et al observed decreased occurrence of a brain state where DMN was activated, while other networks were deactivated (54), a brainstate which resembles the QPP-DMLN observed in this study.…”
Section: Spatial and Temporal Alterations In Dmln Activity In Adsupporting
confidence: 93%
“…These results are consistent with similar observations describing changes in the QPP-DMN + in a recent human study (54). Using dynamic FC analyses in healthy controls and patients with subjective cognitive decline, Liang et al observed decreased occurrence of a brain state where DMN was activated, while other networks were deactivated (54), a brainstate which resembles the QPP-DMLN observed in this study. The analogy between the ndings of Liang et al and the current study suggest similar alterations in DMLN activity are observed in patients with subjective cognitive decline and at pre-plaque stages in the TgF344-AD rat.…”
Section: Spatial and Temporal Alterations In Dmln Activity In Adsupporting
confidence: 93%
“…Accumulating studies have suggested that the brain is intrinsically a dynamic system with discrete model switching rapidly [ 16 ], and dynamic indices based on sliding-window changes may be more informative than static indices [ 17 ]. Recently, studies have shown that SCD exhibits significantly increased fractional windows and mean dwell time [ 18 ] and decreased occurrence frequency [ 19 ] of a DMN-dominated dynamic functional connectivity (dFC) state compared to that of healthy controls. The significant role of dFC in SCD has been gradually recognized, but previous studies were based on whole-brain network-based analyses, and little research has been performed using seed-to-voxel-based analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive evidence suggests that FC, even at rest, should be understood as a dynamic measure. In recent years, dynamic FCs obtained from rs-fMRI time series has proven highly informative regarding the underlying brain connectivity patterns, as it enables slight changes over a short period of time to be explored (18)(19)(20). For example, research based on slidingwindow analysis found that the occurrence frequency of a default mode network (DMN)-dominated dynamic FC state was signi cantly different in SCD patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, dynamic FCs obtained from rs-fMRI time series has proven highly informative regarding the underlying brain connectivity patterns, as it enables slight changes over a short period of time to be explored (18)(19)(20). For example, research based on slidingwindow analysis found that the occurrence frequency of a default mode network (DMN)-dominated dynamic FC state was signi cantly different in SCD patients (20). However, there have been few attempts to directly compare static and dynamic FCs or to determine whether dynamic FCs could undergo stable and subtle changes in subjects with SCD.…”
Section: Introductionmentioning
confidence: 99%